CXCR-4 expression by circulating endothelial progenitor cells and SDF-1 serum levels are elevated in septic patients - Christian Patry; Daniela Stamm; Christian Betzen; Burkhard Tönshoff; Benito A. Yard; Grietje Ch. Beck; Neysan Rafat (BMC, 2018)
Abstract Background Endothelial progenitor cell (EPC) numbers are increased in septic patients and correlate with survival. In this study, we investigated, whether surface expression of chemokine receptors and other receptors important for EPC homing is upregulated by EPC from septic patients and if this is associated with clinical outcome. Methods Peripheral blood mononuclear cells from septic patients (n = 30), ICU control patients (n = 11) and healthy volunteers (n = 15) were isolated by Ficoll density gradient centrifugation. FACS-analysis was used to measure the expression of the CXC motif chemokine receptors (CXCR)-2 and − 4, the receptor for advanced glycation endproducts (RAGE) and the stem cell factor receptor c-Kit. Disease severity was assessed via the Simplified Acute Physiology Score (SAPS) II. The serum concentrations of vascular endothelial growth factor (VEGF), stromal cell-derived factor (SDF)-1α and angiopoietin (Ang)-2 were determined with Enzyme linked Immunosorbent Assays. Results EPC from septic patients expressed significantly more CXCR-4, c-Kit and RAGE compared to controls and were associated with survival-probability. Significantly higher serum concentrations of VEGF, SDF-1α and Ang-2 were found in septic patients. SDF-1α showed a significant association with survival. Conclusions Our data suggest that SDF-1α and CXCR-4 signaling could play a crucial role in EPC homing in the course of sepsis.